On the Piezoelectric Properties of Zinc Oxide Thin Films Synthesized by Plasma Assisted DC Sputter Deposition - Michael McKinlay; Lewis Fleming; Manuel Pelayo García; Lucía Nieto Sierra; Pilar Villar Castro; Daniel Araujo; Basilio Javier García; Des Gibson; Carlos García Nuñez (Advanced Materials Interfaces)
Abstract This work presents a study of piezoelectric zinc oxide (ZnO) thin films deposited by a novel post‐reactive sputtering method. The process utilizes a rotating drum with DC magnetron sputtering deposition onto substrates with subsequent DC plasma‐assisted oxidation of the deposited metal to metal oxide. The paper analyzes the influence of plasmaassisted magnetron sputtering (PA‐MS) deposition parameters (O2 plasma source power, O2 flow, and Ar flow) on the morphological, structural, optical, and piezoelectric properties of ZnO thin films. Design of experiments has been utilized to evaluate the role of these parameters on the growth rate (rg) and the properties of resulting films. Results indicate a predominant influence of the plasma power on the rg over other parameters. Among the eight tested samples, three of them show high crystal quality with high intensity (0001) diffraction peak, characteristic of the wurtzite crystalline structure of ZnO, and one of them exhibits piezoelectric coefficient values of ≈11pC N−1. That sample corresponding to a ZnO film deposited at the lowest rg of 0.075 nm s−1, confirmed the key role of the deposition parameters on the piezoelectric response of films, and demonstrated PA‐MS as a promising technique to produce high‐quality piezoelectric thin films.